Quantifying the high-speed running and sprinting profiles of elite female soccer players during competitive matches using an optical player tracking system - Mara, J. K.; Thompson, K. G.; Pumpa, K. L.; Morgan, S. (The Journal of Strength and Conditioning Research, 2017)
The aim of this study was to determine the high-speed running and sprinting profiles of elite female soccer players during competitive matches using a new Optical Player Tracking system. Eight stationary video cameras were positioned at vantage points surrounding the soccer field so that when each camera view was combined, the entire field could be viewed simultaneously. After each match, an optical player tracking system detected the coordinates (x, y) of each player for every video frame. Algorithms applied to the x and y coordinates were used to determine activity variables for 12 elite female players across 7 competitive matches. Players covered 9,220-10,581 m of total distance, 1,772-2,917 m of high-speed running (3.4-5.3 m/s) distance, and 417-850 m of sprinting (>5.4 m/s) distance, with variations between positional groups (p < 0.001; partial n2 = 0.444-0.488). Similarly, the number of high-speed runs differed between positional groups (p = 0.002; partial n2 = 0.342), and a large proportion of high-speed runs (81-84%) and sprints (71-78%) were performed over distances less than 10 m. Mean time between high-speed runs (13.9 ± 4.4 seconds) and sprints (86.5 ± 38.0 seconds) varied according to playing position (p < 0.001; partial n2 = 0.409) and time of the match (p < 0.001; partial n2 = 0.113-0.310). The results of this study can be used to design match-specific conditioning drills and shows that coaches should take an individualized approach to training load monitoring according to position.